PEMBELAJARAN DALAM JARINGAN DENGAN PENDEKATAN SAINTIFIK BERBANTUAN PLATFORM EDMODO UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMA - Nindy Ivalyn; Andi Pujo Rahadi (ALGORITMA: Journal of Mathematics Education, 2020)
The mathematics problem-solving ability of students in Indonesia is not high yet. The students found it difficult to do the mathematics problems that lead to solving a problem. This study aims to improve students' mathematical problem-solving skills using the Edmodo platform. The study used a quasi-experimental design to find out whether the enhancement of students' mathematical problem-solving abilities that obtain using the Edmodo Platform with a scientific approach is significantly higher than the students who obtain scientific approach learning models. The sample of the research was students in two classes X grade student Negeri 1 Parongpong, West Bandung 2019/2020. The first-class students obtained an using the Edmodo Platform with a scientific approach, while the students in the second class obtained a scientific approach learning with a scientific approach. The results showed that the enhancement of the students' mathematical problem-solving abilities in both classes was included in the moderate category. Based on the statistical tests, the students in the first class have a significant enhancement in mathematical problem-solving abilities compared with the students in the second class. Furthermore, student responses to use the Edmodo Platform with a scientific approach are categorized as "very like" and student responses to a scientific approach are categorized as "very like".